PENGARUH TINGKAT KESEHATAN FINANSIAL PERUSAHAAN TERHADAP PERTUMBUHAN LABA PADA PERBANKAN SYARIAH DI INDONESIA (Studi Kasus Pada Bank Umum Syariah di Indonesia Tahun 2012-2016) - Vivin Ulfiantari Agustina; Abdul Qodir Djaelani; Ahmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThis research aims to determine the effect of health level corporate finance to profit growth of Islamic Banking in Indonesia. Assessment of bank soundness in this research using RGEC for the approach method, which consisting of Risk Profile, Good Corporate Governance, Earnings, and Capital. The population of this research are all syariah commercial banks which registered in Bank Indonesia (BI) on period 2012-2016. The data which used in this research is secondary data. The results showed that the ratio Non Performing Financing (NPF) has not negatively affect on profit growth, while the ratio of Financing to Deposit Ratio (FDR) and Operational Cost of Operating Income (BOPO) has not positive affect on profit growth. The ratio Return On Assets (ROA) has a positive affect on profit growth, while the ratio Capital Adequacy Ratio (CAR) has a negative affect on profit growth. Simultaneously the ratio of NPF, FDR, ROA, BOPO, CAR have significant effect on profit growth. Key words: Financing Soundness, RGEC, Profit Growth.